(untitled) (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Supine hypotension syndrome among parturients during caesarean sections under spinal anesthesia may result in shock which can cause fatal maternal and foetal outcome. Objectives: The aim of study is to compare incidence of supine hypotension syndrome among parturients during caesarean sections under SAB with or without wedge under the right buttock. Methods: Sixty term parturients at childbearing age of a of ASA grade I & II were randomly selected for caesarean sections under SAB and divided equally into two groups: NWG-Non Wedge group (n=30) WG- Wedge group (n=30) In Non Wedge group parturients were kept in supine position without using wedge under right buttock and in Wedge group parturients were tilted 15° left lateral by using wedge under right buttock. Caesarean sections were performed under SAB using minimum effective dose (ED95) of 0.5% hyperbaric bupivacaine(.06mg/cm of height) and parturients were preloaded with isotonic crystalloid solution. Parametric data like pulse, blood pressure among groups were analyzed by ANOVA test. Results: The results revealed that the incidence of supine hypotension syndrome between two groups were not statistically significant. Conclusion: It can be concluded that caesarean sections can be done with hemodynamic stability under SAB without wedge under right buttock among parturients by using minimum effective dose(ED95) of 0.5% hyperbaric bupivacaine (.06mg/cm of height) and after preloading with isotonic crystalloid solution without affecting maternal as well as foetal outcome. In supine position of the patient without wedge the surgeon is more comfortable and gets better operative field. J. Dhaka National Med. Coll. Hos. 2017; 23 (02): 47-50